2010
DOI: 10.1021/cc900176x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Substituted 2-(Benzylthio)imidazo[1,2a]pyrimidin-5-ones

Abstract: A microwave-assisted solid-phase synthesis of 2-(benzylthio)imidazo[1,2a]pyrimidin-5-ones has been developed. Using microwave irradiation, the reaction time was significantly reduced from a few days to 80 min. A representative set of 10 2-(benzylthio)-6,7-substituted-imidazo[1,2a]pyrimidin-5-ones was prepared. These compounds were subsequently N-alkylated and formylated in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Soh et al described the synthesis of 2-(benzylthio)imidazo-[1,2-a]pyrimidin-5(1H)-ones on bromomethyl resin 118. 83 β-Keto ester 117 was reacted with thiourea to afford 5,6disubstituted-2-mercaptopyrimidin-4-one intermediate, which immediately react with resin 118 under microwave irradiation conditions provided resin bound pyrimidines 119. The resin 119 on reaction with bromoacetonitrile resulted in resin 120, which on subsequent self-cyclization with benzyl thiol followed by cleavage from the solid support yielded 2-(benzylthio)imidazo[1,2-a] pyrimidin-5(1H)-ones 121 (Scheme 28).…”
Section: Acs Combinatorial Sciencementioning
confidence: 94%
See 1 more Smart Citation
“…Soh et al described the synthesis of 2-(benzylthio)imidazo-[1,2-a]pyrimidin-5(1H)-ones on bromomethyl resin 118. 83 β-Keto ester 117 was reacted with thiourea to afford 5,6disubstituted-2-mercaptopyrimidin-4-one intermediate, which immediately react with resin 118 under microwave irradiation conditions provided resin bound pyrimidines 119. The resin 119 on reaction with bromoacetonitrile resulted in resin 120, which on subsequent self-cyclization with benzyl thiol followed by cleavage from the solid support yielded 2-(benzylthio)imidazo[1,2-a] pyrimidin-5(1H)-ones 121 (Scheme 28).…”
Section: Acs Combinatorial Sciencementioning
confidence: 94%
“…Soh et al described the synthesis of 2-(benzylthio)­imidazo­[1,2- a ]­pyrimidin-5­(1 H )-ones on bromomethyl resin 118 . β-Keto ester 117 was reacted with thiourea to afford 5,6-disubstituted-2-mercaptopyrimidin-4-one intermediate, which immediately react with resin 118 under microwave irradiation conditions provided resin bound pyrimidines 119 .…”
Section: Solid-phase Synthesis Of Imidazopyrimidinesmentioning
confidence: 99%
“…Mw-assisted synthesis provided fast access to substituted 2-(benzylthio)­imidazo­[1,2- a ]­pyrimidin-5­(1 H )-ones . β-Keto ester 650 (Scheme ) was reacted with thiourea 651 to provide 5,6-disubstituted 2-mercaptopyrimidin-4-ones 652 , which were immobilized onto bromomethyl resin in a one-pot reaction.…”
Section: Cyclative Cleavagementioning
confidence: 99%
“…However, alkylation of tetrahydropyrimidine/di-hydropyrimidine rings using PTC conditions generated S-monoalkylated (2nd position-alkylated derivatives) and/or simultaneous S-and N-dialkylated products (2nd and 3rd position-alkylated derivatives) [29]. Additionally, an attempt of selective N-alkylation (3rd position) of an S-benzylated intermediate yielded both N-and O-dialkylated products (3rd and 4th positions), simultaneously [30]. Furthermore, it has been reported that treatment of methylthiodihydropyrimidines/ methylthiotetrahydropyrimidines with hydrogen sulfide (H 2 S) afforded the corresponding thiouracil derivatives with selective substitution at the 3rd position, i.e., thiooxotetrahydroprimidinones [25].…”
Section: Introductionmentioning
confidence: 99%